TRANSITION TO INNOVATIVE ECONOMICS ON THE BASIS OF «ROAD CARD»: EXAMINATION, EVALUATION, PROSPECTS - A. O. Baklanov; N. I. Komkov; V. S. Romantsov (Модернизация, инновация, развитие, 2016)
The innovative economics model is examined in its interaction with the environment that includes such components as science, society, state, education, business and market as well as safety and court systems. Three main RF economics innovative and active development strategies are suggested and discussed: «resource-export», «resource-science» and «resource-innovation» strategies. Preference is given to the resourceinnovation strategy characteristic with multiple effect resulting from innovations used to update domestic technologies and to restructure the processing and manufacturing industries. An instrument called «Road map» is developed as a set and succession of measures required for Russia to transit to innovative economy.